A Revised Edition of Acts of Assembly and Ordinances Relating to the Borough of Gettysburg, at 62-63, Div. 5, § 9 (1887) - (:unkn) unknown (My University, 1887)
That no person shall keep or have in their possession or cause to be kept within said borough, rock or gun powder, gun or explosive cotton, or other combustible matter likely to prove dangerous, unless the same is preserved carefully and without danger to the citizens in a safe magazine constructed and used solely for that purpose and at a distance of at least 500 feet from any dwelling, and the person offending against this section shall, upon conviction before the burgess or any Justice of the Peace, pay a fine and penalty of twenty dollars. To be collected as all such fines are now by law collectible.
Keywords: GUNPOWDER - STORAGE